2019
DOI: 10.1111/ssqu.12685
|View full text |Cite
|
Sign up to set email alerts
|

Labor Laws and Shadow Economies: A Cross‐National Assessment

Abstract: Objective Toward better understanding the political economy of illicit economy, we examine the impact that labor laws have on illicit economic activity. Specifically, we posit that labor regulations are one of the key prospective benefits associated with formal work, and thus incentivize firms and individuals to participate in the formal, rather than illicit, sector. We further argue that the possible negative effect of labor laws on shadow economies is conditioned by countries’ institutional strength. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
(92 reference statements)
1
9
0
1
Order By: Relevance
“…The selection of the sample is exclusively based on data availability. Following Capasso and Jappelli (2013), Bittencourt et al (2014), Schneider et al (2019), and Blanton and Peksen (2019), we specify the following model: leftinformit=α0+α1lngdppitalicit+α2gdpgrit+α3iitalicnfit+α4gc+itα5fdit+α6lnremit+α7fditxlnremitalicit+εtwhere inform it stands for the informal economy (% of official GDP) in country i at time t , ln gdpp , for GDP per capita (a proxy for the level of economic development), gdpgr it , for GDP annual growth rate (a proxy for economic performance), inf it for inflation rate (a proxy for macroeconomic stability), gc it for government consumption expenditures (% GDP) (a proxy for government size), fd it for financial development, ln rem it for remittances (personal remittances received in current US$), fd it × ln rem it for the interaction term between financial development and remittances and ε t for residual, respectively. GDP per capita and remittances are measured on a logarithmic scale.…”
Section: Model and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of the sample is exclusively based on data availability. Following Capasso and Jappelli (2013), Bittencourt et al (2014), Schneider et al (2019), and Blanton and Peksen (2019), we specify the following model: leftinformit=α0+α1lngdppitalicit+α2gdpgrit+α3iitalicnfit+α4gc+itα5fdit+α6lnremit+α7fditxlnremitalicit+εtwhere inform it stands for the informal economy (% of official GDP) in country i at time t , ln gdpp , for GDP per capita (a proxy for the level of economic development), gdpgr it , for GDP annual growth rate (a proxy for economic performance), inf it for inflation rate (a proxy for macroeconomic stability), gc it for government consumption expenditures (% GDP) (a proxy for government size), fd it for financial development, ln rem it for remittances (personal remittances received in current US$), fd it × ln rem it for the interaction term between financial development and remittances and ε t for residual, respectively. GDP per capita and remittances are measured on a logarithmic scale.…”
Section: Model and Datamentioning
confidence: 99%
“…Turning to the impact of explanatory variables on the informal economy, GDP per capita as a proxy for the level of economic development mitigates informality (Bittencourt et al, 2014; Blanton & Peksen, 2019), thereby its coefficient is expected to be negative.…”
Section: Model and Datamentioning
confidence: 99%
“…The interplay between financial crises and the growth of the shadow sector connoted by historical institutionalism are similar to institutional incongruence theories of the shadow sector. In this perspective, the growth of the shadow economy is viewed as driven by an incongruence or "asymmetry between formal and informal institutions" (Williams et al, 2015:295; see also Williams, 2019;Blanton and Peksen, 2019). More specifically, if the formal market institutions and regulatory structures begin to lose legitimacy among economic actors, they will increasingly consider entry into the informal economy as a viable and legitimate option.…”
Section: Temporary Fix or Lasting Change? The Persistent Impact Of Crisesmentioning
confidence: 99%
“…Previous studies have found many determinants of the shadow economy, including unemployment [ 7 , 8 ]; tax burden [ 9 , 10 ]; corruption [ 11 – 13 ]; trade openness or globalization [ 14 ]. However, our literature review indicates that the relationship between national intellectual capital and shadow economy has largely been neglected in existing empirical studies.…”
Section: Introductionmentioning
confidence: 99%